(untitled) (Bangladesh Rice Journal, 2025)
In irrigated condition, double transplanting (DT) of dry season rice in Potato-Rice-Rice cropping pattern emerges as a promising technology to reduce yield losses associated with late-planted dry season rice. A consecutive three-year experiment encompassing three planting dates (20, 28 February and 08 March) and four seedling ages (45, 60, 75 days, and with 75-day for double transplanting- 35 days in the seedbed and 40 days in the first transplanted plot) was conducted to assess the performance of double-transplanted dry-season rice in comparison to conventional transplanting methods. Across the years, the grain yield of dry season rice exhibited a gradual decline with the advancement of planting time. However, the higher grain yield was consistently found from double transplanted dry season rice in all planting times. The yield advantage from double transplanting was 17%, 13%, and 16% for planting times on February 20, February 28, and 08 March, respectively compared to conventional transplanting. The system productivity of Potato-Double transplanted dry season rice-wet season rice cropping pattern was higher (1-6%) in all planting times compared to the cropping pattern with traditional transplanting method. Double transplanting technology found more stable compared to traditional method in late planting situation. The average added net returns with double transplanted dry season rice over traditional transplanted rice was US139 to US187 ha−1 in 20 February, US67 to US117 ha−1 in 28 February and US68 to US171 ha−1 in 08 March planting. These findings highlight the profitability of adopting double transplanting in the Potato-Rice-Rice cropping system. Bangladesh Rice J.27(1): 13-29, 2023